Drosophila Lipase 3 Mediates the Metabolic Response to Starvation and Aging - Hänschke, Lea; Heier, Christoph; Maya Palacios, Santiago José; Özek, Huseyin Erdem; Thiele, Christoph; Bauer, Reinhard; Kühnlein, Ronald P.; Bülow, Margret H. (Frontiers in Aging, 2022)
The human LIPA gene encodes for the enzyme lysosomal acid lipase, which hydrolyzes cholesteryl ester and triacylglycerol. Lysosomal acid lipase deficiency results in Wolman disease and cholesteryl ester storage disease. The Drosophila genome encodes for two LIPA orthologs, Magro and Lipase 3. We found previously that Lipase 3 transcription is highly induced in mutants with organelle defects. Here we show that Lipase 3 does neither hydrolyze triacylglycerol nor diacylglycerol. We generated a Lipase 3 mutant that accumulates phosphatidylinositol rather than storage lipids. We show that Lipase 3 is drastically upregulated in starved larvae and starved female flies, as well as in aged male flies. Lipase 3 mutants show sex-specific starvation resistance and a trend to lifespan extension. Our study suggests that, in contrast to its mammalian homolog LIPA, Lipase 3 is a putative phospholipase that is upregulated under extreme conditions like prolonged nutrient deprivation and aging.